Numerical simulation of the black sea pollution for the case of the mine waters discharge - Belyaev, M. M.; Kirichenko, P. S. (Science and Transport Progress, 2011)
The 3D numerical model was developed and used to simulate the sea pollution after mine waters discharge. The model is based on the numerical integration of the K-gradient transport model and the model of potential flow. The results of numerical experiment are presented.